Incidence and risk factors for infection in oral cancer patients undergoing different treatments protocols - Panghal Manju; Kaushal Vivek; Kadayan Sangeeta; Yadav Jaya (BMC Oral Health, 2012)
Abstract Background Over the past decade, advances in cancer treatments have been counterbalanced by a rising number of immunosuppressed patients with a multitude of new risk factors for infection. Hence, the aim of this study was to determine risk factors, infectious pathogens in blood and oral cavity of oral cancer patients undergoing different treatment procedures. Methods The present prospective cohort analysis was conducted on the patients undergoing treatment in the radiotherapy unit of Regional Cancer Institute, Pt. B.D. Sharma University of Health Sciences, Rohtak, Haryana, during the period of January 2007 to October 2009. Total 186 patients with squamous cell carcinoma of oral cavity were analyzed in the study. Based on treatment procedures patients were divided into three groups, group I were under radiotherapy, group II under chemotherapy and group III were of radio chemotherapy together. Clinical isolates from blood and oral cavity were identified by following general microbiological, staining and biochemical methods. The absolute neutrophile counts were done by following the standard methods. Results Prevalent bacterial pathogens isolated were Staphylococcus aureus, Escherichia coli, Staphylococcus epidermidis, Pseudomonas aeruginosa, Klebsiella pneumonia, Proteus mirabilis, Proteus vulgaris and the fungal pathogens were Candida albicans, Aspergillus fumigatus. The predominant gram negative bacteria, Pseudomonas aeruginosa and Klebsiella pneumonia were isolated from blood of radiotherapy and oral cavity of chemotherapy treated cases respectively. The predominance of gram positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis) were observed in blood of chemotherapy, radio chemotherapy cases and oral cavity of radiotherapy, radio chemotherapy treated cases. Our study also revealed the presence of C. albicans fungi as most significant oral cavity pathogens in radiotherapy and radio chemotherapy cases. Conclusion Gram positive bacteria and Gram negative were reported from the blood of all the three groups of patients. Oral mucositis played a significant role in oral cavity infection and make patients more prone to C. albicans infection.